Game Based Learning (GBL) Terintegrasi Teknologi Dalam Peningkatan Minat baca Siswa di SDN Kampung Baru - TAUFIK ARRAHMAN; Suriansyah, Ahmad; Budi Harsono, Arta Mulya; Pratiwi, Diani Ayu; Agusta, Akhmad Riyandi (Joyful Learning Journal, 2024)
The problem addressed in this study is the significant changes brought about by the digital era in education, including a decline in students' reading interest due to dependency on technology. Reading skills are essential to support learning and critical thinking. An effort to address this issue is by implementing the Game-Based Learning (GBL) model utilizing technology. The research subjects are fifth-grade students at SDN Kampung Baru, Pelaihari Subdistrict, Tanah Laut Regency, South Kalimantan. The research method used is qualitative with a case study approach, involving the school principal, teachers, and students as participants. The results indicate that GBL creates an enjoyable learning environment, enhances reading interest, and motivates students. This study concludes that the GBL model aligns with contemporary developments by providing digital access and offering an effective approach without burdening students.